The Influence of Corporate Social Responsibility, Company Size, And Profitability on The Value of Mining Sector Companies for the 2016-2020 Period - Kumba Digdowiseiso; Siti Rosyida Cindy (Budapest International Research and Critics University, 2022)
This study aims to analyze the effects of the Corporate Social Responsibility variable measured by the GRI G4 CSR index, the Firm Size variable measured by the Natural Logarithm of total assets, and Profitability proxied by the Return On Assets (ROA) on the firm value measured by the Price Book Value (PBV) of the mining sector over the period 2016-2020. The population in this study includes 46 mining companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used purposive sampling and obtained a sample of 14 companies. This study used secondary data in the form of annual reports, financial reports, and sustainability reports obtained from the Indonesia Stock Exchange which can be accessed through the official website of the Indonesia Stock Exchange, namely www.idx.co.id, and the website of each related company. The analytical technique used in this study uses the STATA 16 program. The results showed that CSR and Firm Size had a negative and insignificant effect on firm value. However, profitability produced a positive and significant effect on Firm Value.